2020
DOI: 10.3389/fimmu.2020.563434
|View full text |Cite
|
Sign up to set email alerts
|

A Mineralocorticoid Receptor Deficiency in Myeloid Cells Reduces Liver Steatosis by Impairing Activation of CD8+ T Cells in a Nonalcoholic Steatohepatitis Mouse Model

Abstract: Background and AimsThe mineralocorticoid receptor (MR) and renin-angiotensin-aldosterone system (RAAS) are implicated in non-alcoholic liver fatty disease (NALFD). However, inflammatory mechanisms linking MR and RAAS with disease pathology remain unclear. Here we aimed to evaluate the contribution of myeloid MR to the inflammatory response in an animal model of non-alcoholic steatohepatitis (NASH), induced with a methionine-choline deficient diet (MCD).MethodsMice with a conditional deficiency of MR in myeloid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 58 publications
1
13
0
Order By: Relevance
“…Zhang et al (2017) further demonstrated, that the MR directly regulated the estrogen receptor 1 (ERα) in macrophages, which thereby via hepatocyte growth factor (HGF)/Met signalling enhanced lipid accumulation and reduced insulin sensitivity of hepatocytes. These data are in agreement with a study from Munoz‐Durango et al (2020) demonstrating in a NASH model that mice with a myeloid cell‐specific MR inactivation showed reduced hepatic inflammation and lower triglyceride content than controls. While the total number and percentage of liver inflammatory infiltrate cells were similar in both mutants and controls, expression of the co‐stimulatory molecule CD86 by dendritic cells and the CD25 activation marker in CD8 + T cells were significantly reduced in myeloid‐specific mutant livers.…”
Section: Mr In Liver Diseasessupporting
confidence: 93%
“…Zhang et al (2017) further demonstrated, that the MR directly regulated the estrogen receptor 1 (ERα) in macrophages, which thereby via hepatocyte growth factor (HGF)/Met signalling enhanced lipid accumulation and reduced insulin sensitivity of hepatocytes. These data are in agreement with a study from Munoz‐Durango et al (2020) demonstrating in a NASH model that mice with a myeloid cell‐specific MR inactivation showed reduced hepatic inflammation and lower triglyceride content than controls. While the total number and percentage of liver inflammatory infiltrate cells were similar in both mutants and controls, expression of the co‐stimulatory molecule CD86 by dendritic cells and the CD25 activation marker in CD8 + T cells were significantly reduced in myeloid‐specific mutant livers.…”
Section: Mr In Liver Diseasessupporting
confidence: 93%
“…Myeloid cells MR KO has been studied in kidney (31), heart (32,33), and liver disease (34). In a non-alcoholic steatohepatitis model, myeloid cells MR KO decreased fibrosis (34). Similarly, in a progressive glomerulonephritis model, myeloid cells MR KO reduced kidney damage and inflammation (31).…”
Section: Discussionmentioning
confidence: 99%
“…However, smooth muscle cells specific MR KO prevented ischemia-reperfusion induced AKI, via the inhibition of lipid peroxydation (6). Myeloid cells MR KO has been studied in kidney (31), heart (32,33), and liver disease (34). In a non-alcoholic steatohepatitis model, myeloid cells MR KO decreased fibrosis (34).…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study performed in methionine-choline deficient diet (MCD) animals it has been reported that proinflammatory cells are functionally suppressed in the absence of MR. This loss might modulate the adaptive immune response, eventually leading to a reduction in lipid accumulation in the liver ( 27 ).…”
Section: Mechanisms Of Inflammationmentioning
confidence: 99%